Frazeologizm czarna dziura / черная дыра w słownikach oraz tekstach współczesnego języka polskiego i rosyjskiego - Miturska-Bojanowska, Jolanta (Acta Polono-Ruthenica, 2019)
In the second half of the last century the English term black hole was borrowed into Polish and Russian. Soon, secondary meanings began to appear predominantly in journalistic texts. They have been partially recorded in linguistic dictionaries. The aim of this paper is to show the secondary meanings of the phrase czarna dziura / чернаядыра listed in dictionaries as well as those present only in Polish and Russian texts.